Criminal Sanctions For Paternal Molestation Against Underage Biological Child: A Juridical Review Of The Verdict Of The District Court Of The Republic Of Indonesia Number (1041 K/Pid.Sus/2020) - Irvan Fadjar Satrio; Amiludin; Undang Prasetya Umara (Jurnal Inovasi dan Kreativitas (JIKa), 2023)
Problem: Family life is the foundation of society where individuals unite in love and responsibility to create a safe environment for the development of children. In this context, the role of parents is very important, because it has a big impact on children's physical, emotional, and social aspects. In this discussion, the importance of the role of parents in shaping children's futures will be explored. Children have special needs and protections under criminal law, with specific age limits defining their status as minors. Crimes against minors, such as sexual abuse, are a serious problem because children are still vulnerable and less able to protect themselves. The case of sexual abuse by a biological father against a biological child in the decision of the District Court of the Republic of Indonesia resulted in criminal sanctions based on the child protection law. This punishment reflects legal efforts to protect children's rights and provide appropriate sanctions to perpetrators. Purpose: The aim of this research is to understand how criminal sanctions are applied to perpetrators of sexual abuse by biological fathers of underage biological children based on the Child Protection Law. Methodolgy: This research uses a doctrinal approach which is normative in nature, or normative juridical legal research, or normative legal research which is basically an activity that will research aspects to resolve a problem that exists within the internet of positive law Keywords: Criminal Act, Obscenity, Sexual Violence